Implementation of Bantul Regent Policy Number 18 Year 2016 Regarding Smoke Free Healthy Areas - Totok Sundoro; Parmadi Sigit Purnomo; Pramukti Dian Setianingrum (Journal of Governance and Public Policy, 2020)
Smoking results in the emergence of diseases with a risk of 2 up to 4 times as much as coronary heart disease and has a higher risk of lung cancer and another non-contagious disease. There is a higher percentage as much 21.2% for population aged ≥ 10 years who smoke every day in the Special Region of Yogyakarta. The policy of the smoke-free areas at school is regulated by Bantul Regent Regulation No. 18, 2016. The purpose of this research is to find out the aspects of communication, resources, disposition, and bureaucratic structure in policy implementation. The study was conducted at MAN 3 Bantul using descriptive qualitative methods through interviews and observations. Validity checking is carried out by the triangulation method. The results showed that the implementation of the policy of smoke-free areas in schools had not been the provisions. The communication process by doing the installation of a smoking ban sign and conducting socialization, but it has not involved the authorities yet. In implementing the policy, it is not supported by adequate resources and the commitment of the leaders by establishing policies and SPOs. The support in the aspect of communication in the form of posters for smoking restrictions and dispositions in the form of reprimand sanctions. While the inhibiting factors in the aspect of communication in the form of policy rules, resources in the form of teams, the budget disposition in the form of lack of awareness, reluctance to reprimand, and bureaucratic structure in the form of SPO also did not yet exist for smokers at schools.